Bronchogenic Cyst: a rare cause of respiratory distress in neonate - A Case Report - Meshram, Rajkumar M.; Apte, Mohini; Bhongade, Swapnil (Indian Journal of Case Reports, 2017)
Bronchogenic cyst is an unusual congenital pulmonary malformation which may occur at various sites of tracheobronchial tree as well as unusual ectopic site like cervical, scapular region, pericardium and abdomen. Newborn with large cyst can develop respiratory distress, cyanosis and feeding difficulty. A 37 day old male infant presented with failure to thrive, feeding difficulty, respiratory distress and cyanosis. His chest radiograph was suggestive of shift of mediastinum and heart with hyperinflatted left lung. CT thorax showed minimal enhancing cystic lesion posterior to trachea and its bifurcation on right side, it was compressing the right main bronchus. The cyst was successfully surgically excised which was adhering to carina and intrabronchial extension and its histopathological finding confirmed the bronchogenic cyst. Though, bronchogenic cyst is rare cause of respiratory distress, cyanosis, and failure to thrive and feeding difficulty, it should be considered one of the differential diagnoses.